Pengaruh BPHTB Dan PBB Terhadap Pendapatan Asli Daerah Kabupaten Nagan Raya - Joni Saputra (Akbis: Media Riset Akuntansi dan Bisnis, 2023)
This study aims to examine and analyze the effect of Acquisition Duty of Right on Land and Building and Land and Building Tax on Original Local Government Revenue of Nagan Raya Regency for the period 2017-2021 (Case Study on the Nagan Raya Regional Financial Management Agency). This research is a quantitative study with a total sample of 20 data. In this study, data were taken from realization reports over a period of 5 years, processed and analyzed using Multiple Linear Regression Tests. To test the hypothesis using the coefficient of determination that has been adjusted with the t and F tests. The results of this research data indicate that the Fee for Acquisition Duty of Right on Land and Building has a positive and significant effect on Original Local Government Revenue. Land and Building has a positive and significant effect on Original Local Government Revenue of Nagan Raya Regency.